The Impact of Village Cash Transfer on Rural Households’ Economic Well-being - Alan Sutisna; Riatu Mariatul Qibthiyyah (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2023)
Indonesia applied adjustments and refocused the policy of using the Village Funds budget to minimize the impact of the Covid-19 pandemic in 2020, especially in the rural area. The Village Funds have been used as a social safety net as Village Cash Transfer. The researchers carried out this study to present an overview of the evaluation of the effects of Village Cash Transfer on the economic well-being of rural communities in every household quintile. This study uses data on the characteristics of 35,759 households obtained from merging results of the March & September 2020 Susenas data with the Village Fund data in each district/city area. Data were analysed using Smoothed Instrumental Variables Quantile Regression, which overcame endogeneity issues and produced robust estimates. The study results show that the Village Cash Transfer has a positive and significant impact on the economic well-being of rural households. Still, their impact is felt more by the upper middle quintile households, which benefit more from Village Cash Transfer households in the Java region. As a result, it is advisable for Governments to be more generous in providing benefits to families in the lowest quantile and to monitor the program by the requirements of beneficiaries closely.